(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The study involved 59 2nd year students of VSMU. The course of speleoclimatotherapy consisted of 10 sessions of 60 minutes each and was carried out in a stationary ground speleochamber at a temperature of 18–22 °C. All subjects signed an informed consent to participate in the study. Before the start of speleotherapy, on the 3rd, 10th day of speleotherapy and 7 days after the end of the course, we recorded the psychological parameters, simple visual-motor reaction, heart rate and rheoencephalogram of students. The dynamics of these parameters under the influence of speleotherapy, the corrective effect of speleo on the body and the correspondence of a number of obtained changes to the adaptation theory were revealed. Separately, multidirectional changes in cardiac rhythm parameters under the influence of speleotherapy were noted.